Numerical simulation of steel-foamed concrete composite wall panels - Prabha, P.; Palani, G.S.; Senthil, R.; Marimuthu, V.; Saravanan, M.; Surendran, M. (Journal of Structural Engineering, 2025)
Finite element analysis (FEA) is performed to develop reliable models to simulate the behaviour of steel-foamed concrete composite panel under axial loading. The test data and the results conducted earlier at CSIR-SERC on composite wall panels made of outer thin cold formed steel sheeting with infill light weight foamed concrete (LFC) under compression loading are adopted. The FE model is validated by comparing the load-deformation behaviour and the ultimate capacity obtained from FEA with that of experimental investigation. It is observed that the FE model is capable of predicting the initial stiffness and ultimate failure load with an overestimation of around 11%. The FE model is used for further parametric studies with varying number of studs and steel sheet thickness to study their influence on the behaviour.